Can we identify the salt-cocrystal continuum state using XPS? - Tothadi, Srinu; Shaikh, Tabrez Rafique; Gupta, Sharad; Dandela, Rambabu; Vinod, Chathakudath P.; Nangia, Ashwini K. (Crystal Growth & Design, 2021)
X-ray photoelectron spectroscopy (XPS) is used to understand the nature of acid-base crystalline solids, to know whether the product is a salt (proton transfer, O-center dot center dot center dot H-N+) or a cocrystal (neutral adduct, O-H center dot center dot center dot N). The present study was carried out to explore if intermediate states of proton transfer from COOH to nitrogen (the proton resides between hydrogen bonded to O and N, O center dot center dot center dot H center dot center dot center dot N, quasi state) can be differentiated from a salt (complete proton transfer, N+-H center dot center dot center dot center dot O-) and cocrystal (no proton transfer, O-H center dot center dot center dot N) using N 1s XPS spectroscopy. The intermediate states of proton transfer arise when the pK(a) difference between the acid and the conjugate base is between -1 and 4, -1 < Delta pK(a) < 4, a situation common with COOH and pyridine functional groups present in drug molecules and pharmaceutically acceptable coformers. Complexes of pyridine N bases with aromatic COOH molecules in nine salts/cocrystals were cocrystallized, and their N 1s core binding energies in XPS spectra were measured. The proton state was analyzed by single-crystal X-ray diffraction for confirmation. Three new complexes were crystallized and analyzed by XPS spectra (without knowledge of their X-ray structures), to assess the predictive ability of XPS spectra in differentiating salt-cocrystal intermediate states against the extremities. The XPS results were subsequently confirmed by single-crystal X-ray data. Complexes of 3,5-dinitrobenzoic acid and isonicotinamide in 1:1 and 1:2 ratios exist as a salt and a salt-cocrystal continuum, respectively, as shown by the N 1s core binding energies. The proton states of the crystalline solids by XPS are in good agreement with the corresponding crystal structures. Other complexes, such as those of 3,5-dinitrobenzoic acid with 1,2-bis(4-pyridyl)ethylene, exhibit a salt-cocrystal continuum, maleic acids with 1,2-bis(4-pyridyl)ethylene and acridine are salts, 2-hydroxybenzoic acid and acridine is a salt, and the complex of 3,5-dinitrobenzoic acid and 3-hydroxypyridine is a salt and salt-cocrystal continuum, while fumaric acids with 1,2-bis(4-pyridyl)ethylene and acridine are cocrystals. Furthermore, three new acidbase complexes of 3,5-dinitrobenzoic acid with phenazine, 4-hydroxypyridine, and 4-cyanopyridine were studied initially by XPS and then confirmed by X-ray diffraction. In summary, since the N 1s binding energies cluster in a narrow range as cocrystals (398.7-398.9 eV) and salts (400.1-401.1 eV), it is clearly possible to differentiate between cocrystals and salts, but the saltcocrystal continuum values in XPS spectra are clustered in an intermediate range of cocrystals and salts but overlap with those of cocrystal or salt binding energies.

Multicomponent solvate crystals of 3,5-dinitrobenzoic acid and acetamide and CSD analysis of solvates - Shaikh, Tabrez Rafique; Shelke, Nikita; Tothadi, Srinu (ACS Omega, 2023)
Twelve multicomponent solvate crystals (cocrystal solvates) of 3,5-dinitrobenzoic acid and acetamide were synthesized via slow evaporation method. All crystalline materials were characterized by single-crystal X-ray diffraction. All cocrystal solvates are isostructural, and crystal packing forms continuous channels where some solvent molecules are connected via weak intermolecular interactions with 3,5dinitrobenzoic acid and acetamide. All multicomponent solvate crystals encompass amide-amide dimer homo synthons and form R22 (8) motifs. Moreover, the phase purity of solvate crystals was analyzed by powder Xray diffraction. Further, most of the cocrystal solvates were analyzed by nuclear magnetic resonance and differential scanning calorimetry. Cambridge structural database analysis categorizes solvate propensity in single-crystal structures. The importance of hydrogen bond donor/ acceptor nature, size, and shape of solvents is also discussed in the context of crystallization and crystal packing.
Keywords: Co-Crystals; Design; Host Guest Complex; solvent

Continuous flow solvent-free and catalyst-free mechanochemical production of rhodamine B dyes and their derivatives - Purohit, Mukesh; Shaikh, Tabrez Rafique; Kulkarni, Amol A. (Chemical Communications, 2025)
In this communication, we have described a simple and efficient, catalyst free and solvent-free protocol for the continuous flow synthesis of rhodamine B dyes developed from 3-diethyl amino phenol and phthalic anhydride. Nearly 95% conversion was achieved within 12 min using a jacketed single screw reactor. This method is further used for the synthesis of six derivatives with 70-84% yield, which can be compared to 85% yield from a 1-hour long batch synthesis involving a catalyst.